Language and Tenor of President Muhammadu Buhari’s Speech on Covid-19 Pandemic - Aroge, Modupe Grace; Irewole, Michael Olayinka (NIU Journal of Humanities; Vol 5 No 2 (2020): KIU Journal of Humanities, Vol. 5 No. 2, June 2020, 2020)
The study examined the language and tenor of President Muhammadu Buhari’s Speech on covid-19 pandemic to the general populace. It explored the metadiscourse features and tenor of three President Muhammadu Buhari’s covid-19 pandemic speeches given around 29 th of March – 27 th April, 2020. This was in view to describe the nationwide broadcast given by the president during the pandemic to sensitize the general public and reveal the government’s plan, measure to be adopted to stop the spread of the pandemic, and concern of the government for the masses during lockdown period of covid-19 pandemic.The data were drawn from the President Muhammadu Buhari’s Speeches on covid-19 pandemic  from the internet. The three speeches on covid-19 pandemic were read to bring out the interactive and interactional metadiscourse features and the tenor of the speaker. The analysis of the data was guided using Hyland (2006) Theory on metadiscourse with Eggins’ (1994) sub-classification of tenor continuum in interactions. The study revealed that the language of the speeches was formal. It was showed that while all the interactive and interactional metadiscourse elements such as hedges, boosters, self-inclusion, attitude markers and range of other writer-oriented markers of engagement in the speech were used in the speeches for the listeners’ understanding. The tenor of the speaker and the listeners indicated that of unequal power; the social distance showed that the speaker and listeners have a kind of frequent contacts with one another during the pandemic through the broadcast. There was a numerical preponderance of interactive devices where transitional markers were most frequently subcategory used to show the importance of cohesion and coherence in formal speech. It was also discovered that the President used declarative sentences as a way of giving information to the audience and also for creating a natural conversational phenomenon between the president and the listeners so that the general populace could understand the intended message(s). The study concluded that examining nationwide broadcast given during this pandemic through the language use, metadiscourse elements, and tenor of discourse aid comprehension of the intended message being passed across to the audience. Keywords : President’s speech, Covid-19 pandemic, tenor of discourse, metadiscourse elements